Avaliação de desempenho da ferramenta cerâmica mista tipo "S" no torneamento do aço ABNT 4140 endurecido - Nicolodi, Jeferson Hilário Wallendorff (2016)
The present work shows the performance evaluation of the mixed ceramic tool, type "S", on the ABNT 4140 hardened steel turning (55HRC). The influence of cutting parameters were investigated (cutting speed and feed rate) on the tool failure, cutting forces and surface roughness. A full factorial design of experiment was used to conduct and analyze the results. The results show that higher cutting speeds and feed rates to have more prominent effect on tool life. The parameter of greater influence on the cutting force and the surface roughness was the feed rate. Crater and the nose wear (VBc) occurred in all cutting conditions. The tool wear mechanisms predominant were diffusion, abrasion and adhesion (attrition). The equation of the tool life curve was established for the machining conditions to providing the optimization of this process in the future.